Synthesis of geopolymers from industrial wastes for sustainable construction - Lee, Kelvin Kai Wen (2024)

(untitled)
In the current era of rapid development, the construction sector is thriving due to the increasing global population. Cement, a fundamental construction material, is extensively utilized in large quantities. However, the high demand for cement leads to heightened production rates, resulting in significant energy consumption and environmental harm due to elevated carbon emissions. Concurrently, the escalating human population has led to a surge in waste generation from various activities, exacerbated by events such as the Covid-19 pandemic, which bolstered production in medical-related industries like glove manufacturing. Recycling glass poses challenges due to its intricate sorting and cleaning processes, rendering it impractical. In pursuit of a more sustainable future aligned with Sustainable Development Goals (SDGs) and circular economy principles, the invention of green substitute cement has emerged. To address waste generation challenges and harness the potential of geopolymers, this research study was undertaken. Geopolymer paste was synthesized by replacing traditional binders with glove former waste (GFW) and colored glass waste bottles (GW), alongside pulverized fly ash. Various mix designs, including 100FA, 10GW, 20GFW, 30GFW, 40GFW, 10GW, 20GW, 30GW, and 40GW, were synthesized into 50mm cubes and cylinders and subjected to ambient curing at room temperature for testing at 7th, 14th, and 28th day intervals. Laboratory tests, including compressive strength, water absorption, porosity, FESEM, FTIR, XRD, and sieve analysis, were conducted throughout the study. Results indicated that all mix designs met the standards' requirements. Despite potential impacts on strength and performance due to increased substitution of GFW and GW, results exceeded mandated standards. Optimum replacements for GFW and GW were determined to be 30%. Specifically, vii 30GFW yielded 68.513MPa compressive strength, 3.199% water absorption, and 9.70% porosity, while 30GW exhibited 73.971MPa compressive strength, 2.811% water absorption, and 8.78% porosity, as validated by FESEM images. Carbon estimation for OPC paste was 0.35kg per unit compared to zero carbon emissions for geopolymer paste, affirming geopolymer paste as a green substitute for OPC across various construction sector facets. In conclusion, the synthesized waste geopolymer represents a significant step towards sustainability within the construction industry. By utilizing waste materials, it aligns with numerous Sustainable Development Goals (SDGs) and embraces the principles of the circular economy. This innovative approach not only addresses environmental concerns but also contributes to social and economic development, highlighting its potential as a green substitute for traditional construction materials.